Toward a Nuanced Understanding: Faculty Barriers to Navigating Academic Integrity Violations - Scurr, Cory; Mangahis, Carla; Mandal, Julie (Canadian Perspectives on Academic Integrity, 2025)
This study presents the early results of an all-faculty survey conducted at one Ontario Polytechnic institution wherein the focus is on barriers encountered by faculty in the course of navigating and filing academic integrity violations (AIVs). While the general findings corroborate previous work, this research reveals that the number of years a faculty member has taught influences the barriers they experience. These findings have important implications for institutions as they suggest they should consider implementing a more targeted approach to conversations and assurances depending on the number of years a faculty member has taught.